2002
DOI: 10.1084/jem.20020009
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Defect in T Cell Production of Interleukin (IL)-13 in the Absence of Both IL-5 and Eotaxin Precludes the Development of Eosinophilia and Airways Hyperreactivity in Experimental Asthma

Abstract: Interleukin (IL)-5 and IL-13 are thought to play key roles in the pathogenesis of asthma. Although both cytokines use eotaxin to regulate eosinophilia, IL-13 is thought to operate a separate pathway to IL-5 to induce airways hyperreactivity (AHR) in the allergic lung. However, identification of the key pathway(s) used by IL-5 and IL-13 in the disease process is confounded by the failure of anti–IL-5 or anti–IL-13 treatments to completely inhibit the accumulation of eosinophils in lung tissue. By using mice def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
218
2
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 247 publications
(234 citation statements)
references
References 56 publications
(75 reference statements)
8
218
2
5
Order By: Relevance
“…Although IL-13 is mainly produced by T cells [39,40], several sources of IL-13 have been suggested, including human and mouse NK cells [16,17], NKT cells [41], basophils [25,26] and mast cells [42]. To specifically address the question of which cell populations produce IL-13 during this IL-4/B7-independent in vivo immune response to T. muris, we performed cell sorting and quantitative RT-PCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although IL-13 is mainly produced by T cells [39,40], several sources of IL-13 have been suggested, including human and mouse NK cells [16,17], NKT cells [41], basophils [25,26] and mast cells [42]. To specifically address the question of which cell populations produce IL-13 during this IL-4/B7-independent in vivo immune response to T. muris, we performed cell sorting and quantitative RT-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous findings support this concept and further suggest that IL-13 can mediate resistance to T. muris in the absence of both IL-4 signaling and B7 costimulation [8]. These studies indicated either a novel B7-independent pathway of CD4 + T cell differentiation leading to IL-13 but not IL-4 expression or an alternative cell source that can differentiate to produce IL-13 if B7 is blocked and/or IL-4 is neutralized.Although IL-13 is mainly produced by T cells [39,40], several sources of IL-13 have been suggested, including human and mouse NK cells [16,17], NKT cells [41], basophils [25,26] and mast cells [42]. To specifically address the question of which cell populations produce IL-13 during this IL-4/B7-independent in vivo immune response to T. muris, we performed cell sorting and quantitative RT-PCR.…”
mentioning
confidence: 99%
“…[12,13] Eosinophils express MHC class-II molecules, relevant co-stimulatory molecules (CD40, CD28, B7.1 and B7.2) and secrete an array of cytokines capable of promoting lymphocyte proliferation, activation and Th1 or Th2 polarization (IL-2, IL-4, IL-6, IL-12, IL-10). [11,[14][15][16][17] Further eosinophil-mediated damage is caused by toxic hydrogen peroxide and halide acids generated by EPO and by superoxide generated by the respiratory burst oxidase enzyme pathway in eosinophils. Eosinophils also generate large amounts of the LTC 4 , which is metabolized to LTD 4 and LTE 4 .…”
Section: Function Of Eosinophilia In the Gastrointestinal Systemmentioning
confidence: 99%
“…Th1-related cytokines include interferon gamma (IFN-γ), which affects the severity of asthma [4], and interleukin 12 (IL-12), which induces Th1 cells and suppresses Th2 cells [5,6]. Th2-related cytokines include IL-4, IL-5, IL-13, and Th17-related cytokines (tumor necrosis factor-alpha (TNF-α) IL-6, and IL-1β) [7].…”
Section: Introductionmentioning
confidence: 99%